Study Underground flow of Great Caucasian rivers within in Azerbaijan - Farda Imanov; Irada Aliyeva (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The use of underground water for drinking water supply has increased over the recent years, due to intensive pollution of local and transboundary rivers in the Greater Caucasus region of Azerbaijan. In addition to relatively deep groundwaters, undergroundflow of rivers are also widely used for the purpose. The purpose of the present study is to analyze the condition of undergroundflow of rivers in the region and to determine its territorial distribution patterns.